ANALISIS TANGGAPAN KONSUMEN TERHADAP PELAYANAN JASA PERUM PEGADAIAN BUKATEJA PURBALINGGA - Pribadi, Prayoga (Pro Bisnis, 2008)
The title of This research is âConsumers Response Analisis to the Service of Perum Pegadaian Bukateja Purbalinggaâ. This Research has a purpose to know the factor what ever that is most dominant toward the customerâs response. The marketing is the key from all the activities that are carried out by the company especially in achieving the level of the high sale. The number of financial agencies in Indonesia is demanded to give the service extra to the consumers, one Of them the Perum Pegadaian Bukateja in this case the consumer really pays attention to all the services that is given by the Perum Pegadaian Bukateja, this is linked tight whether the consumer will use the product that is offered the Perum Pegadaian Bukateja or not.